Signos estructurales ponderados del perfil de riesgo para el diagnóstico rápido y precoz de ambliopía en niños de 6 años Trujillo -peru - García Carranza, Manuela Violeta (2005)
With the objective to propose a weighed structured model which can make a fast and precocious amblyopia diagnostic. During 2002 and 2003 a prospectic study had been carried out in a random form to 580 of 6 years old student of both sex, Trujillo city. It’s been done a 23 questions interview and a visual sharpness study by the snellen chart. Main outcome measures: Risk amblyopia the weighed evaluation of structurals sing of children with a record more than 50. Amblyopia it’s been considerated as corrected visual acuity < 20/40 (<0.5) in the affected eye not attributable to any underling structural abnormality an the eye, or visual pathway together with > 2 lines difference visual acuity between the eyes. Visual impairment (any visual acuity): Was defined as: ≤ 20/40 (≤ 0.5) and, the difference visual acuity ≥ 2 lines between the eyes. Results: 1. In the logistic regression analyses interview of the 23 variables the signs that have correlation with amblyopia are: eyelids semi closes trating to see (point of 30) traumatism post childbirth with lose of conscience (point 18), constants blinks (points 13), lack of night vision (point 12), covers eye to watch (points 11), watch too close the T.V set (points 9), migraine frequently (point 7). Total points: that are relationed with acuity visual impairment is 100. 2. The amblyopia children were. 3. It’s been identified that 268 (46.25%) women and 312 (53.75%) men have visual sharpness diminution in 37.31% and 33.33% respectively. Finally the weighed structural signs study and the visual impairment it’s been noticed that are more risk of amblyopia when the score is near 100.